THE INFLUENCE OF FINANCIAL DISTRESS, AUDIT FEES, AND COMPANY SIZE ON THE INTEGRITY OF FINANCIAL REPORTS - Muhamad Eko Ariwibowo; Siarwi Siarwi; R.Mohd Zamzami; Rananda Septanta (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to determine the effect of Financial Distress, Audit Fees, and Company Size on the Integrity of Financial Statements. This type of research uses quantitative methods. The population used in this study is Property and Real Estate Companies listed on the IDX for the period 2019-2023. The sampling technique uses Purposive Sampling to determine the most suitable criteria in this study. The criteria have been determined for 29 companies. The data analysis technique uses multiple linear regression with the help of Eviews 12 Software. The results of this study simultaneously Financial Distress, Audit Fees, and Company Size have a significant effect on the Integrity of Financial Statements. While partially Financial Distress has a significant effect on the Integrity of Financial Statements, Audit Fees do not affect the Integrity of Financial Statements, and Company Size does not affect the Integrity of Financial Statements.